Monetary Incomes of Health Professionals in Sverdlovsk Region in 1955-1960 - V. N. Mamyachenkov (Научный диалог)
The article is devoted to the subject insufficiently developed in the national historiography. The study is conducted on materials of several archives: archive of Alexander N. Yakovlev, State archive of Sverdlovsk region, current archive of Territorial body of Federal state statistics service for Sverdlovsk region and the Centre of documentation of public organizations of Sverdlovsk region with the assistance of the scientific and publicistic literature. The relevance of the topic is determined by its importance for the social sciences, especially for history and sociology. Scientific novelty of the work is seen in the fact that the new materials discovered by the author in these archives are introduced into scientific usage. The article aims to study the level and dynamics of the monetary income of relatively little investigated category of the population - health professionals. It is noted that the figures of monetary incomes of actually lived citizens are hidden in the archival collections and working with them requires from the researchers a certain stock of patience, dedication, and most importantly - time. It is argued that the statistical authorities of the Soviet Union conducted systematic surveys of the population periodically changed both a set of indicators of the material situation of the population and the surveyed categories of population themselves. It is stated that in relation to such categories of people as teachers in primary and secondary schools, doctors and the average medical personnel the statistical agencies are confined to obviously non-representative samples. It is stated that the category of health workers in the budget surveys of the population was represented by three sub-categories: doctors, average and younger medical personnel. The latter subcategory was never surveyed by the statistics. It is declared that doctors had the highest wages in the studied period. The salary of the average medical personnel was lower than not only the salaries of doctors, technical workers (engineers) and skilled workers, but also even unskilled representatives of the proletariat. The conclusion is that the level of monetary income of health workers was insufficient for a full prosperous life.